2015
DOI: 10.19028/jtep.03.1.73-80
|View full text |Cite
|
Sign up to set email alerts
|

Edible Coating Nanocomposites to Maintain Quality of Minimally-Processed Snake Fruit

Abstract: PendahuluanBuah salak pondoh merupakan salah satu jenis buah tropis asli Indonesia yang terkenal di daerah Sleman, Yogyakarta. Salak pondoh ini banyak digemari konsumen termasuk dari luar negeri karena mempunyai rasa yang manis, renyah dan sebagai salah satu sumber nutrisi. Salak mengandung zat gizi dan antioksidan yang sebanding dengan kiwi (Gorinstein 2009 Quality parameters measured were on the weight loss, browning index, the hardness, and sensory evaluation. The result showed that antimicrobial activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Widaningrum et al (2015) stated that packaging or coating can inhibit respiration rate and suppress fruit softening. Several studies also reported that NP-ZnO -based coatings and packaging are able to delay the decrease in fruit hardness such as jujube (Li et al, 2009), kiwi (Meng et al, 2014) and salaca (Marpaung et al, 2015).…”
Section: Hardnessmentioning
confidence: 98%
See 1 more Smart Citation
“…Widaningrum et al (2015) stated that packaging or coating can inhibit respiration rate and suppress fruit softening. Several studies also reported that NP-ZnO -based coatings and packaging are able to delay the decrease in fruit hardness such as jujube (Li et al, 2009), kiwi (Meng et al, 2014) and salaca (Marpaung et al, 2015).…”
Section: Hardnessmentioning
confidence: 98%
“…This is because the presence of NP-ZnO in the coating polymer can improve the mechanical properties of the polymer used. coatings were able to reduce weight loss of salak fruit better than controls (Marpaung et al, 2015;Sabarisman et al, 2015). In this research process, jackfruit is stored at room temperature.…”
Section: Weight Lossmentioning
confidence: 99%